2010
DOI: 10.1038/ejhg.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of carrier testing in families after cystic fibrosis diagnosis through newborn screening

Abstract: Newborn screening (NBS) for cystic fibrosis (CF) provides the opportunity for cascade carrier testing of relatives. Uptake of testing by adult non-parent relatives of children diagnosed with CF through NBS has not been previously described, and this study describes uptake by both parents and adult non-parent relatives in Victoria, Australia. Pedigrees were taken from parents of children who were born in 2000-2004 and diagnosed with CF. A total of 40 families were eligible for the study and 30 (75%) were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…This study determined that 16% of at-risk family members had carrier testing after the diagnosis of a child with CF through the Victorian newborn screening program. 11 This proportion is comparable to the percentage of family members tested for FXS (18%, 95% CI 10.8 to 24.7), HD (17%, 95% CI 10.7 to 24.0), and SMA (11%, 95% CI 8.3 to 13.4). The strength of the study by McClaren et al 11 lies in the confirmation of the probands' pedigrees by the probands' parents, ensuring accurate family histories inclusive of relatives whose risk of carrying CF is 1/8 and therefore an accurate estimation of the proportion of family members tested for their CF carrier status.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This study determined that 16% of at-risk family members had carrier testing after the diagnosis of a child with CF through the Victorian newborn screening program. 11 This proportion is comparable to the percentage of family members tested for FXS (18%, 95% CI 10.8 to 24.7), HD (17%, 95% CI 10.7 to 24.0), and SMA (11%, 95% CI 8.3 to 13.4). The strength of the study by McClaren et al 11 lies in the confirmation of the probands' pedigrees by the probands' parents, ensuring accurate family histories inclusive of relatives whose risk of carrying CF is 1/8 and therefore an accurate estimation of the proportion of family members tested for their CF carrier status.…”
Section: Discussionmentioning
confidence: 61%
“…11 This proportion is comparable to the percentage of family members tested for FXS (18%, 95% CI 10.8 to 24.7), HD (17%, 95% CI 10.7 to 24.0), and SMA (11%, 95% CI 8.3 to 13.4). The strength of the study by McClaren et al 11 lies in the confirmation of the probands' pedigrees by the probands' parents, ensuring accurate family histories inclusive of relatives whose risk of carrying CF is 1/8 and therefore an accurate estimation of the proportion of family members tested for their CF carrier status. However, the consequence of using this method resulted in the inclusion of only 30 of the 82 (37%) families whose children were diagnosed with CF between the 1 January 2000 and 31 December 2004.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This is particularly relevant if they are planning a pregnancy but is less so if they are not of reproductive age, do not have a partner, or have finished reproducing. 20 Although most carriers stated that they informed family members of their carrier status, a study by McClaren et al 97 evaluating cascade testing after a child is diagnosed with CF through NBS showed that identifying an individual as a carrier of CF usually results in an average of only 11% of family members being tested.…”
Section: Discussionmentioning
confidence: 99%
“…In an audit of cascade carrier testing after a diagnosis of CF through newborn screening, only 11.8% of eligible (non-parent) (82/716) relatives were tested [218]. These same researchers also showed that in a clinical setting, the diagnosis of a baby with CF by newborn screening "does not lead to carrier testing for the majority of the baby's non-parent relatives" [219]. This is incredibly unfortunate, given that predictions of any reliability ought to include the prior probability of someone being born in that 'ancestry group' with the mutations and phenotype of interest.…”
Section: Prenatal Diagnosis Preimplantation Genetic Diagnosis/screenmentioning
confidence: 99%